Analyzing Islamic Financial Asset Growth in Indonesia Through Sharia Fund Asset Growth - Andriani, Marina; Isfiyanti , Silvia; Rahmawati, Rima Siti; Mutiaulfah , Syifa; Ruminarasa, Sri Tesa; Irfanudi, Naufal Zaidan (Islamicate Institute, 2025)
The rapid expansion of Islamic finance in Indonesia has signaled a shift in national economic dynamics, driven in part by the rising role of sharia-compliant financial instruments. Among these instruments, sharia funds have emerged as a critical vehicle for financial inclusion and asset growth, particularly within the framework of Islamic ethical investment. This study aims to analyze the patterns, performance, and strategic development of Islamic financial asset growth in Indonesia through the lens of sharia fund asset expansion. Utilizing qualitative and document-based analysis, the research examines relevant financial policies, market behavior, and investor responses that shape the current trajectory. It addresses key research questions related to the mechanisms of sharia fund contribution, structural advantages, and institutional challenges. The findings highlight the centrality of sharia funds in boosting Islamic financial assets and underscore the policy and management implications for sustainable financial development. The study contributes conceptually to the discourse on Islamic financial markets and offers practical insights for future strategic planning.